Ferulic Acid Ameliorates Atherosclerotic Injury by Modulating Gut Microbiota and Lipid Metabolism - Gu, Yuyan; Zhang, Yaxin; Li, Mei; Huang, Zhiyong; Jiang, Jing; Chen, Yihao; Chen, Junqi; Jia, Yuhua; Zhang, Lihua; Zhou, Fenghua (Frontiers in Pharmacology, 2021)
Lipid metabolism is dysregulated in the pathogenesis of atherosclerosis. The gut microbiota has been strongly implicated in lipid deposition in atherosclerosis. Herein, we examined the effects and molecular mechanisms involving ferulic acid (FA) in atherosclerosis using the ApoE-knockout (ApoE-∕-, c57BL/6 background) mouse model. Eighteen male ApoE-/- mice were fed a high-fat diet (HFD) for 12 weeks and then randomly divided into three groups: the model group (n=6), the FA (40 mg/kg/day) group (n=6) and simvastatin (5 mg/kg/day) group (n=6). Treatments lasted 12 weeks. Six male c57BL/6 mice fed a common diet acted as the control group. Plaques were quantified using Oil Red-O and Masson trichrome staining. Fresh fecal samples (5 to 8 pellets/mouse) were collected one days before the sacrifice of mice, gut microbiota were detected by 16S rRNA sequencing, and fecal metabolites were analyzed by 1H NMR spectroscopy. The effects of FA on serum lipids were also investigated. Expression of lipid metabolism-related genes and proteins were determined by real time quantitative PCR and western blotting, respectively. After treatment for 12 weeks, we found FA significantly alleviated atherosclerosis and regulated lipid levels in mice. Furthermore, liver function and hepatocyte steatosis were also mitigated by a FA diet. FA improved lipid metabolism involving up-regulation of AMPKα phosphorylation and down-regulation of SREBP1 and ACC1 expression. Furthermore, FA induced marked structural changes in the gut microbiota and fecal metabolites and specifically reduced the relative abundance of Fimicutes, Erysipelotrichaceae and Ileibacterium, which were positively correlated with serum lipid levels in atherosclerosis mice. We show that FA treatment protected against atherosclerosis may partly through modulation of gut microbiota and lipid metabolism, likely involving activation of the AMPKα/SREBP1/ACC1 pathway.